Quelle place pour la durabilité dans les représentations sociales de la mobilité ? Vers une meilleure compréhension des actions mises en œuvre - Julien Schiebel (Développement Durable et Territoires)
By determining social representations of mobility, this article allows a better understanding of the actions undertaken by the stakeholders of mobility. Moreover, it allows us to define the place of sustainability beyond that displayed in public discourses. In order to contribute to this theoretical reflection, semi-directive interviews (n = 29) were carried out with various mobility actors in the Luxembourg cross-border area and made it possible to collect these representations. The results attest to the limitation of sustainability to its economic and then environmental vision, while the social aspect is only partially present. In another approach of sustainability by stakeholders, "to move more efficiently" and "to move differently" are the main issues of the mobility. At the opposite, the concept of "move less" is almost absent from representations, opening the way to the need for a broader approach to mobility than its simple "move" component.